Management of Obstructive Sleep Apnea Syndrome in Obese Children - Vina Rosalina; Maria Mexitalia; Dwi Wastoro (RSUP Dr. Kariadi, 2013)
Background : Obstructive Sleep Apnea Syndrome (OSAS) is strongly associated with obesity. The common presenting complaints are excessive daytime sleepiness and loud snoring which potential for significant comorbidity of metabolic syndrome and decreasing in quality of life. Case : An 11-year-old obese boy was refereed to Dr. Kariadi Hospital with complaints of fatique and frontal headache. His mother reported the loud snoring, apneic events during the night, excessive daytime sleepiness, increased irritability, and difficulty of school learning. Imaging studies showed cardiomegaly, adenoidal/nasopharyngeal ratio 0.714; opaque mass on cervical and airway space narrowing. Tympanometric audiogram showed mild right conductive hearing loss. The patient was diagnosed with OSAS, chronic and hypertrophic adenotonsillitis, severe hypertension, dilated right ventricle, right conductive hearing loss, obesity. The boy was undergone adenotonsillectomy and management of weight lossed. Antihipertensive and other supportive medication were given and good results. Discussion : The recommended initial treatment, even in obese children, consists of surgical removal of the adenoids and tonsils.5,6 Several studies have shown that adenotonsillectomy reverses the symptoms and confirm the beneficial effects for OSAS on children's growth, school performance, improvements in PSG, behavior, QoL and cardiac function. The success rate for adenotonsillectomy in the context of OSA was approximately 85%. Conclusion : Adenotonsillectomy and weight reduction is considered to be the primary intervention for OSAS children. Because the case had also severe hypertension, antihypertensive and other supportive medicine were give and had a good result. Keywords : OSAS, obesity, children, adenotonsillectomy